(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The quality of public services and the yield of organizations are not limited to the financial investment and innovation solely. Human capital plays a critical role in the growth and excellence in institutions, but its contribution remains dependent on several factors. Its role is not limited on quantitative and qualitative accumulating, because it should be coherent and integrated in the development process. The theories of endogenous growth contributed to account for the disparity in levels of development between countries, by assuming that the extent of human capital response or inversely lack of responsiveness the economic system. This inaction is usually the prime cause of the deterioration of the quality of service and lack of satisfaction of the citizens, in addition of the lack of employee satisfaction about the circumstances of his work. Hence, arose the significance of several research about the mechanisms of reducing non-enthusiasm for the job or complacency professional and indifference. Staff of Jazan University has been chosen as a context of the empirical investigation of this study. The data has been collected using a well designed questionnaire and analyzed by SPSS program.